Reproductive Aspects of Lemuru Fish (Sardinella Lemuru) Landed at PPI Tanjung Luar East Lombok as Enrichment Material for Zoology Subjects - Lidia Zindarti Nurmia; Karnan Karnan; Mahrus Mahrus (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Sardinella lemur is a pelagic fish with the most population in Indonesia, precisely in the Bali Strait. This study aims to determine the reproductive lemurs of lemurs fish (S. lemur) that landed at PPI Tanjung Luar East Lombok as enrichment material for zoology subjects. This research was conducted in January-March 2023, taking place in Tanjung Luar, East Lombok. This study used lemurs fish (S. lemurs) with a total sample of 188 individuals, 56 females, and 132 males. This research is included in the quantitative descriptive research with PCAS sampling. Data was collected by measuring body length, weighing body weight, calculating sex, classifying TKG, and analyzing GMI. It is estimated that the lemurs spawn in April-June with reference to TKG and IKG. TKG analysis by observing the morphology and weighing the gonad weight of the fish while the IKG compares the gonad weight and body weight multiplied by 100%. The TKG found ranged from TKG I to TKG V with the dominant sex being male. The highest TKG was found in March for females who were pregnant while TKG for males with developed gonads. From the results of the data analysis, the highest female sex index was obtained in February 3.5% and the lowest was in March 0.3% male. The results of observations of the highest average body length of lemurs fish were in February at 15.75 cm and the lowest in March at 15.04 cm. Based on the body weight of lemurs fish, the highest was in February at 33.03 gr and the lowest was in Marat ch 30.63 gr. Based on the results of the research and discussion it can be concluded that lemurs fish in the waters of Tanjung Luar, gonads mature for lemurs fish in March and are expected to spawn from April to June.